2003
DOI: 10.1053/jhep.2003.50266
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Pharmacodynamic Action of Budesonide in Early– and Late–Stage Primary Biliary Cirrhosis

Abstract: Budesonide has been discussed as a potential treatment option in primary biliary cirrhosis (PBC). Therefore, we studied the pharmacokinetics and pharmacodynamics of budesonide in patients with PBC stage I/II and stage IV. Twelve patients with early PBC stage I/II and 7 patients with PBC stage IV under continuous treatment with ursodeoxycholic acid (UDCA) were enrolled in an exploratory trial. Each patient received oral budesonide for 3 weeks at weekly increasing dosages of 3 mg once to thrice per day. Budesoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
89
0
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(95 citation statements)
references
References 28 publications
1
89
0
4
Order By: Relevance
“…Our previous pharmacokinetic study with budesonide revealed that budesonide should not be administered in late-stage PBC because of unpredicted side effects. 27 Rifampicin is used as second-line therapy for controlling pruritus in PBC. [36][37][38] It is a potent inducer of intestinal and hepatic CYP3A via activation of the pregnane X receptor/steroid and xenobiotic receptor.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our previous pharmacokinetic study with budesonide revealed that budesonide should not be administered in late-stage PBC because of unpredicted side effects. 27 Rifampicin is used as second-line therapy for controlling pruritus in PBC. [36][37][38] It is a potent inducer of intestinal and hepatic CYP3A via activation of the pregnane X receptor/steroid and xenobiotic receptor.…”
Section: Discussionmentioning
confidence: 99%
“…Thereafter, each patient was treated with UDCA capsules (15 mg/kg daily, divided into a morning and an evening dose) for 3 weeks (days 2-22) and subsequently with rifampicin dragées (600 mg/d, evening dose) for 1 week (days [23][24][25][26][27][28][29]. Administration of 3 mg budesonide was repeated on study days 22 and 29.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it should be noted that transaminitis in PBC may in part be a feature of hepatocyte injury from the effects of cholestasis. Of note, portal vein thrombosis has been reported as a complication in up to 29% of patients with advanced liver fibrosis [Hempfling et al 2003], precluding budesonide use in patients with cirrhosis. Due to concerns over side effects, evidence supporting the benefit of prednisolone is lacking, and although some restitution in serum and histological markers of liver inflammation has been documented [Mitchison et al 1992], these findings have not translated into improved patient outcomes.…”
Section: Alternative and Adjuvant Therapiesmentioning
confidence: 99%